DESCRIPTION OF THE CHARACTERISTICS OF NATIONAL HEALTH INSURANCE PARTICIPANTS THAT USE FIRST LEVEL HEALTH FACILITIES - ngesti utami (STIKes Kepanjen, 2023)
Puskesmas and JKN are two things that are interrelated in the health service system in Indonesia. The Puskesmas also has a role as a provider of health services to JKN participants, namely the role of carrying out health efforts. Research data from (Taufiqul et al., 2017) the factor of the type of JKN participant that has a relationship with the characteristics of JKN participants who utilize health services at the health center are PBI participants with 73.38% of respondents. The number of visits utilizing health services in 2019 was 19,272 visits (Malang District Health Profile, 2020). Based on the number of patient visits that utilize health services, it can be shown that there are patients who have easy access to health services. With the number of patient visits, it will be a challenge for health service providers that the increase in patients must still pay attention to the quality of health services at the puskesmas. This study aims to describe the characteristics of JKN participants who utilize FKTP services at the Ardimulyo Health Center based on the type of participant, age and medical diagnosis. The population in this study are JKN participants who utilize health services at the Ardimulyo Health Center in 2021, totaling 2,574 participants. With a sample of 346 JKN participant respondents who utilized FKTP services at the Ardimulyo Health Center, registered at the Ardimulyo Health Center health facility aged >65 years and willing to become respondents. Data is presented in the form of frequency distribution tables, percentages, and accompanied by explanations. The results of this study are that the most types of PBI participants utilize FKTP services. The age of JKN participants who make the most use of FKTP services is the age range of 56-65 years which is included in the late elderly category. The most common diagnosis is the diagnosis of